A forecast of relevant pediatric sedation trends. Issue 1 (March 2016) - Mahmoud, Mohamed A.; Mason, Keira P.
Abstract : Purpose of review: Over the past decade, the field of pediatric sedation has benefited from contributions which include the introduction and update of policies, procedures, and guidelines regarding training, physiologic monitoring and delivery, the approval of new sedatives, the multispecialty collaborations intended to advance the field and the development of sedatives, and delivery systems. This review will explore new drug innovations as well as evolved formulations of already approved agents, unique sedative delivery systems, the clinical application of pharmacogenetics and will conclude with a reflection on the current and future trends and focus of pediatric sedation research. Recent findings: In recent years, the number of diagnostic and therapeutic procedures performed on children in nonoperating room anesthetizing locations has exploded at a rate which has in many instances, outpaced the availability of anesthesiologists. Over the past decade, the search for safe and effective sedatives and delivery systems has been embraced by all sedation providers. Dexmedetomidine and fospropofol were recently introduced, along with a computer-assisted personalized sedation delivery system which empowers the patient to assist in his own sedation. The evolution of target-controlled infusion systems with both open and closed-loop design are intended to more precisely deliver sedation using pharmacokinetic models specific for each sedative. New formulations of propofol, ketamine, etomidate, and benzodiazepines are in development, all striving to improve predictability, safety, and recovery profile. Pharmacogenetics is being explored for its role in the effects of analgesics, sedatives, and local anesthetics. Summary: As the demand for procedural sedation continues to expand, the sedation providers must continue to be creative in their search for novel, safe, effective, and efficient methods to deliver care. Approaching the field of sedation as a science is essential for the clinicians and researchers who strive to tailor the sedation to the patient and the procedure.